Pengaruh Pelarut N-Heksan, Etil Asetat, Dan Etanol 96% Terhadap Kadar Flavonoid dan Aktivitas Antioksidan Kulit Buah Lamtoro (Leucaena leucocephala) - ina bulu, atalia tamo; Novembrina, Metrikana (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Lamtoro rind waste in Indonesia is produced in large quantities so it can become a problem for the environment if not managed properly. Lamtoro rind extract contains chemical compounds such as flavonoids, alkaloids, saponins, phenolics, and tannins. Flavonoid compounds, one of the phenolic groups widely found in plant tissues, can act as antioxidants. This study aims to examine the effect of N-hexane, ethyl acetate, and 96% ethanol on the levels of flavonoids and the antioxidant activity of lamtoro rind (Leucaena leucocephala). Lamtoro rind was made simplicial and extracted by maceration method using N-hexane, ethyl acetate, and 96% ethanol separately for 3x24 hours. Each extract was analyzed to determine the levels of flavonoids by UV-Vis spectrophotometry method and antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhidrazyl) method. The results of the analysis showed that 96% ethanol gave the extract with the highest levels of flavonoids, followed by ethyl acetate and N-hexane of 15.345 µg/g, 14.899 µg/g and 10.234 µg/g respectively. In addition, the antioxidant activity of lamtoro rind extract was also shown to be higher in 96% ethanol extract compared to ethyl acetate extract and n-hexane extract calculated with IC50 values of 39.914 ppm, 30.788 ppm, and 164.304 ppm respectively. Based on this study, it can be concluded that 96% ethanol resulted in lamtoro rind extract with higher levels of flavonoids and stronger antioxidant activity compared to using N-hexane or ethyl acetate as solvents. These results indicate that lamtoro rind has the potential as a useful source of flavonoids and antioxidants.